67 PHARMACOLOGY AND TOXICOLOGY OF A NEW AQUEOUS FORMULATION OF INTRAVENOUS AMIODARONE (AMIO-AQUEOUS) IN COMPARISON TO CORDARONE IV. (1st March 2005) - Somberg, J. C.; Cao, W.; Cvetanovic, I.; Ranade, V.; Molnar, J.
Abstract : Background: Hypotension is the most frequent adverse event reported with intravenous amiodarone (Cordarone IV). The hypotension has been attributed to the vasoactive solvents of the formulation, polysorbate 80 and benzyl alcohol, both known to exhibit negative inotropy and hypotensive effect. A new aqueous formulation of intravenous amiodarone (Amio-Aqueous) does not contain vasoactive excipients and may be less toxic and causes less hypotension than Cordarone IV. This hypothesis was tested in a series of animal studies with direct comparison of Amio-Aqueous and Cordarone IV. Methods: Four studies were performed in anesthetized Sprague Dawley rats weighing between 450 and 550 grams: 1) the lethal dose 50% (LD50) and lethal dose 100% (LD100) were determined in 6 rats for each drug; 2) the effects of the two drugs on myocardial contractility were compared at 5, 10 and 20 mg/kg doses using a Walton-Brody strain gauge (n = 30); 3) the effects of the drugs on arterial blood pressure were compared at doses of 3, 5, 10, and 20 mg/kg (n = 10); 4) the antiarrhythmic effects were compared at doses between 0.5 and 20 mg/kg following left anterior descending coronary artery ligation (n = 12). The studies were conducted in accordance to the NIH Guide for the Care and Use of Laboratory Animals. Results: The acute toxicology study showed that both LD50 and LD100 were 30% greater for Amio-Aqueous than for Cordarone. At the dose where all animals expired on Cordarone, 50% of animals were still alive on Amio-Aqueous. The study on myocardial contractility showed that Amio-Aqueous was far less negative inotropic than Cordarone IV (p<0.001). Amio-Aqueous did not have an effect on contractility at 5 and 10 mg/kg dose levels while Cordarone resulted in a 25% (p<0.01) and 29% (p<0.002) decrease, respectively. The study on arterial blood pressure showed that Cordarone caused a significant decrease in blood pressure at each of the 3, 5, 10, and 20 mg/kg dose (p<0.05 to p<0.001) while Amio-Aqueous did not. The study on the antiarrhythmic effects showed comparable efficacy for both formulations. Conclusions: Cordarone IV was more toxic, caused significant hypotension and negative inotropy, while Amio-Aqueous lacked the hypotensive and cardiotoxic properties of Cordarone IV. Therefore Amio-Aqueous is safer than Cordarone IV and the generic formulations.